Barriers to and expectations of performing physical activity in female subjects with Type 2 Diabetes - A. J. van Rooijen; P. Rheeder; C. J. Eales; H. M. Molatoli (AOSIS, 2002)
The aims of the study were to establish in a cohort of female patients with Type Diabetes the knowledge and perceptions of exercise, personal and environmental barriers to doing exercise and the outcome expectations of performing physical activity. The sample consisted of 28 patients between the ages of 48 and 70 (mean = 60.2, SD = 6.6) years and 11 ethnic groups, attending the Mamelodi Hospital Diabetic Outpatient Clinic. The duration of the disease ranged from 1 to 22 years and 82% of the patients were using oral hypoglycaemic agents. Demographic and qualitative data were captured by means of focus group interviews. Demographic data were summarized with descriptive statistics. Qualitative data were analysed by means of well described principles of qualitative data analyses. A percent agreement was performed, and data were re-coded until the inter-rater reliability was 85%. All 28 subjects reported that they saw doing household chores and walking as ways of exercising. Sixty one percent of the subjects indicated relief from arthritis as a benefit of exercise. The main environmental barrier was the absence of a convenient venue (61%). Tiredness (36%) and arthritis (36%) were the main personal barriers to doing exercise. All subjects indicated a better quality of life and improvement of functional capabilities as outcome expectations of taking part in an exercise program. Subjects had positive attitudes towards exercise, wanted to have control in the program and also expressed the need for social support.